Studies on the Juvenile Hormone Extracts of the Butterfly Terias hecabe Linné (Lepidoptera). - Nayar, K. K. (Contributions to Entomology = Beiträge zur Entomologie, 1961)
1. Diethyl ether-extracts of whole abdomen of adults of Terias hecabe Linn., (Lepidoptera: Pieridae) were made to test the juvenile hormone-effects of the same. - 2. Experiments were done on caterpillars and pupae of Terias, involving injection and topical application of the extracts. - 3. A high rate of mortality occurred when injections were given. All pupae died, while about 5.6% of the caterpillars alone pupated, when injections were made. In two exceptional cases, indications of prolegs were noticeable on the abdomen of the pupae as tanned swellings. - 4. Topical application on skin of caterpillar, followed by sealing with paraffin ("wax tests") showed no effect on the insects and the larvae moulted into normal pupae and adults. But topical application on pupae produced on the adult skin an absence of true scales on the treated area. Instead the patches showed intermediates between scales and setae arranged sparsely like pupal setae. - 5. Application of extracts on amputated surface of metathoracic legs of caterpillars, resulted in the production of stumplike regenerates in the adult butterflies. These regenerates were bilobed, with a setabearing ventral organ, resembling a larval thoracic leg. - 6. The findings have been discussed in the light of recent literature on juvenile hormone and its physiology.